Verifikasi Biologis Dan Kesehatan Reproduksi Calon Mempelai Pra Perkawinan Dalam Perspektif Hukum Islam - Fitriyani (Al Ashriyyah, 2019)
This study describes the biological verification and reproductive health of prospective pre-marriage brides in the perspective of Islamic law, and covers Islamic insights regarding the verification of biological and reproductive health of pre-marriage brides, and the law to conduct biological verification and reproductive health for pre-marriage brides in legal perspective Islam. The case that took place in Bulukumba on September 17, 2017 was related to biological forgery between Syarifah Nurul Husna (20 years) and Rahmat Yani (28 years old) a woman from Erelebu Hamlet, Eka Tiro Village, Bontotiro District, Bulukumba Regency. Apparently married to fellow women, he was involved with same-sex marriage. Revealed when the first night after the wedding ceremony took place, finally arrived where the moment of the two lovebirds got together in the first night. Suddenly Nurul Husna screamed and ran out of her room, she was crying out unconsciously knowing that Rahmat Yani was actually a woman. Syarifa Nurul Husna's family did not remain silent over the incident that happened to her daughter, they then made a vote on her daughter-in-law's identity. After doing the checkup, he finally found out if Rahmat Yani was Rahmayani according to the residents of Herlang Hamlet, from the village of Rahmat Yani. For the sake of the sanctity of the marriage institution, similar events are expected not to occur again in the future. For this reason, a solution needs to be formulated, including fixing civil administration regulations. This study seeks to discuss one solution, which includes verification of identity and reproductive health as one administrative requirement for marriage. If it refers to the quantity of cases, this idea might be considered as an excessive response. However, when viewed from the classical fiqh perspective, this has been exemplified in the early days of the development of Islamic Law. Presupposition cases born from the leaders of four popular schools indicate that there is no need to wait for cases to establish the law. For example, the priests of the school of thought have spoken and determined the legal consequences of a clogged vagina or a penis being cut off for marital survival This research is a descriptive research (library research) with a type of qualitative research, using a legal approach (formal juridical), a case approach, a fiqh approach and a psychological approach. The theory used is Maqasyid syariah related to the maintenance of offspring popularized by As-Sya tiby and the benefit theory that was popularized by at-Tufi.